PEMETAAN MANAJEMEN PEMBINAAN SEKOLAH SEPAKBOLA (SSB) DI KOTA PADANG - Zaid Tholhah,; Didin Tohidin,; Nugroho Susanto,; andri gemaini, (Jurnal IKEOR, 2023)
This study aims to find out how the management of Soccer School (SSB) is doing in Padang City Because nothing is known about the management of Padang City Soccer School (SSB). The method used is a survey with data collection methods using a questionnaire This study involved a football school sponsored by PSSI in Padang City, with 30 people from 19 SSBs. Samples taken from all sampling results The instrument used is a questionnaire Descriptive percentages are used in data analysis. Based on the research results of Football School Management Mapping (SSB) in Padang City, it is known that the mean value is 3.19 and the good criteria is 80%. It is known that the mean value of the planning variable is 3.21 with a percentage of 80%, the mean value of the organizational variable is 3.27 with a percentage of 82%, the mean value of the guiding variable is 3.17 with a percentage of 79%, management /enforcement variable has a mean value of 3.09 with a percentage of 77%, supervision subvariable has a mean value of 3.06 with a percentage of 76%, and evaluation subvariable has a mean value of 3.34 with a percentage of 83%.